Clarity, clinical applicability and relevance of absolute contraindications in official 'Summaries of Product Characteristics' (SmPCs) - Andrikyan, Wahram; Then, Melanie; Dürr, Pauline; Jung-Poppe, Lea; Schuster, A.; Weisbach, L.; Farker, K.; Fromm, Martin; Maas, Renke (EUROPEAN JOURNAL OF CLINICAL PHARMACOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-08

Comprehensibility of Contraindications in German, UK and US Summaries of Product Characteristics/Prescribing Information-A Comparative Qualitative and Quantitative Analysis - Then, Melanie; Andrikyan, Wahram; Fromm, Martin; Maas, Renke (Journal of Clinical Medicine, 2022)
Contraindications (CIs) in Summaries of Product Characteristics (SmPCs)/Prescribing Information (PI) that lack clarity may pose a risk to medication safety and increase the risk for adverse drug reactions. We assessed and compared SmPCs/PI from three major drug markets regarding comprehensibility from the prescriber perspective, as well as usability in clinical decision support systems. 158 drugs met the following inclusion criteria: marketed in Germany (DE), United Kingdom (UK) and United States (US) and belonged to the 100 most recently FDA approved and/or 100 most frequently prescribed drugs in either country. In the 474 (3 x 158) SmPCs/PI all expressions for absolute CIs were identified, divided into 3999 stand-alone terms and evaluated according to 'clarity' and 'codability'. The average number of absolute CIs per drug differed drastically between the three markets (DE: 11.7, UK: 9.0, US: 4.6). Expressions were frequently unclear (DE: 27.2% (95% CI 25.2-29.2%), UK: 28.5% (26.2-30.9%), US: 22.6% (19.7-25.8%)). Moreover, 60.9% (58.6-63.1%), 63.6% (61.0-66.0%), and 64.7% (61.2-68.1%) of the expressions were not codable in DE, UK, and US, respectively. Taken together, in three major drug markets, statements regarding CIs in SmPCs/PI substantially differ in frequency and frequently lack clarity and codability which poses an unnecessary obstacle to medication safety.
CRIS-Team WoS Importer:2022-08-12

Development in Prescriptions of Contraindicated and Potentially Harmful QT Interval-Prolonging Drugs in a Large Geriatric Inpatient Cohort From 2011 to 2021 - Then, Melanie; Tuemena, Thomas; Sledziewska, Anna; Gassmann, Karl-Guenter; Maas, Renke; Fromm, Martin (Clinical Pharmacology & Therapeutics, 2023)
Regulatory authorities put major emphasis on QT (interval)-prolonging properties of new molecular entities. Product information/Summaries of Product Characteristics (SmPCs) of multiple drugs contain warnings or contraindications regarding QT prolongation, e.g., on coadministration of QT-prolonging drugs (QT drugs). To characterize the development of the QT drug burden, we performed a trend analysis of prescriptions and co-prescriptions of QT drugs in a large geriatric inpatient cohort. The German SmPCs (status of 2014 and of 2021) and the year-wise listings in the CredibleMeds((R)) database from 2011 to 2021 were used as sources. There were 402,631 geriatric cases included. The group of QT drugs according to SmPCs in 2014, which must not be combined with other QT drugs, was less frequently involved in contraindicated co-prescriptions in 2021 compared with 2015 (3.0% (2.5-3.7%) of cases with at least one of those drugs in 2021 vs. 4.0% (3.5-4.5%) in 2015), with citalopram, escitalopram, and amiodarone involved in nearly 90% of the co-prescriptions. The number of CredibleMeds-QT-drugs per patient increased from 0.4 (SD=1.1) in 2011 to 1.8 (SD=3.9) in 2021. The percentage of contraindicated co-prescriptions of drugs with known risk for torsade de pointes according to CredibleMeds((R)) listings at the beginning of the respective years increased from 1.7% in 2011 to 6.1% in 2021. Considering the regularly updated CredibleMeds((R)) QT drugs list, the contraindicated co-prescriptions of QT drugs markedly increased in the last decade. If prescribers considered only the few most frequently (co-) prescribed QT drugs, then most of the medication errors regarding QT drugs could be prevented.
CRIS-Team WoS Importer:2023-01-27

Identification of diagnosis-related contraindications based on the medication plan alone - Andrikyan, Wahram; Then, Melanie; Gaßmann, Karl-Günter; Tuemena, T.; Dürr, Pauline; Fromm, Martin; Maas, Renke (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2022)
CRIS-Team WoS Importer:2022-04-15

Inconsistencies of absolute drug-drug contraindication reports: Analysis of Summaries of Product Characteristics of commonly prescribed drugs - Weisbach, Laura; Schuster, Anna K.; Hartmann, Michael; Dürr, Pauline; Then, Melanie; Andrikyan, Wahram; Fromm, Martin; Maas, Renke; Farker, Katrin (British Journal of Clinical Pharmacology, 2023)
Aims: Prescribing information should follow a defined structure to help prescribers easily find required information. Often information appears in different sections of Summaries of Product Characteristics (SmPCs) in an inconsistent way. Still unknown is how this inconsistency affects absolute contraindications and how it can be improved. Thisstudy aimed to evaluate the structure of absolute contraindications in SmPCs based on absolute drug-drug contraindications (DDCI) in the section 'contraindications' and references to sections 'special warnings and precautions for use' (here as 'warnings') and 'interaction with other medicinal products and other forms of interaction' (here as 'interactions').
CRIS-Team WoS Importer:2023-05-26
Keywords: drug safety; SmPCs; drug–drug contraindications; prescribing information

Prescription of QT interval prolonging drugs in Germany and discrepancies between their Summary of Product Characteristics and the international CredibleMeds((R)) database - Then, Melanie; Andrikyan, Wahram; Maas, Renke; Fromm, Martin (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2022)
CRIS-Team WoS Importer:2022-04-15

The CredibleMeds® list: Usage of QT interval prolonging drugs in Germany and discordances with prescribing information - Then, Melanie; Andrikyan, Wahram; Maas, Renke; Fromm, Martin (British Journal of Clinical Pharmacology, 2021)
Aims: A substantial number of Summaries of Product Characteristics (SmPCs)/Prescribing Information (PI) have warnings or contraindications on QT interval prolongation. The goal of this work was to quantify usage of QT interval prolonging drugs according to the CredibleMeds® database of the German outpatient drug prescription market and to evaluate discrepancies between German SmPCs/US PI and CredibleMeds®. Methods: Drugs listed on CredibleMeds® with known, possible or conditional risk for torsade de pointes were evaluated from 2000 to 2020. The German drug prescription report was used as source for defined daily dose- (DDD-) based prescriptions of the German outpatient drug prescription market of the public health insurance system. German SmPCs and US PI of 253 CredibleMeds®-listed drugs were evaluated for contents regarding QT interval prolongation. Results: Of the drugs currently listed on CredibleMeds®, 59.7% (95% confidence interval [CI] 53.5–65.5%) were listed after 2012. Due to newly listed drugs, the proportion of DDDs of CredibleMeds® drugs among all prescriptions increased from 4.6% in 2013 to 21.1% in 2019. DDD-based usage of the CredibleMeds® drugs already listed in 2013 was similar in 2019. Among the drugs with known QT risk according to CredibleMeds®, 7.5% (95% CI 2.6–19.9%) of German SmPCs and 21.1% (95% CI 11.1–36.3%) of US PI had no mention of QT issues whatsoever. Conclusion: A significant proportion of all drugs prescribed in the outpatient sector is associated with QT risks according to CredibleMeds®. SmPCs and PI should systematically be evaluated for concordance with the widely used CredibleMeds® database to increase medication safety.
CRIS-Team Scopus Importer:2021-07-30
Keywords: medication safety; prescribing information; QT interval; QT prolongation; Summaries of Product Characteristics; torsades de pointes

The Prevalence of Potentially Inappropriate Medication in Geriatric Inpatients According to the PRISCUS 2.0 List - Then, Melanie; Deutsch, Birgit; Tümena, Thomas; Thürmann, Petra A.; Fromm, Martin; Gaßmann, Karl Günter; Maas, Renke (Deutsches Ärzteblatt international, 2023)
CRIS-Team Scopus Importer:2023-11-03

Use of medication data alone to identify diagnoses and related contraindications: Application of algorithms to close a common documentation gap - Andrikyan, Wahram; Then, Melanie; Gaßmann, Karl-Günter; Tuemena, Thomas; Dürr, Pauline; Fromm, Martin; Maas, Renke (British Journal of Clinical Pharmacology, 2022)
Aims: Automated checks for medication-related problems have become a cornerstone of medication safety. In many clinical settings medication checks remain confined to drug–drug interactions because only medication data are available in an adequately coded form, leaving possible contraindicated drug–disease combinations unaccounted for. Therefore, we devised algorithms that identify frequently contraindicated diagnoses based on medication patterns related to these diagnoses. Methods: We identified drugs that are associated with diseases constituting common contraindications based on their exclusive use for these conditions (such as allopurinol for gout or salbutamol for bronchial obstruction). Expert-based and machine learning algorithms were developed to identify diagnoses based on highly specific medication patterns. The applicability, sensitivity and specificity of the approach were assessed by using an anonymized real-life sample of medication and diagnosis data excerpts from 3506 discharge records of geriatric patients. Results: Depending on the algorithm, the desired focus (i.e., sensitivity vs. specificity) and the disease, we were able to identify the diagnoses gout, epilepsy, coronary artery disease, congestive heart failure and bronchial obstruction with a specificity of 44.0–99.8% (95% CI 41.7–100.0%) and a sensitivity of 3.8–83.1% (95% CI 1.0–86.1%). Using only medication data, we were able to identify 123 (51.3%) of 240 contraindications identified by experts with access to medication data and diagnoses. Conclusion: This study provides a proof of principle that some key diagnosis-related contraindications can be identified based on a patient's medication data alone, while others cannot be identified. This approach offers new opportunities to analyse drug–disease contraindications in community pharmacy or clinical routine data.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Anatomical Therapeutic Chemical Classification System; ATC; contraindication; ICD; International Statistical Classification of Diseases and Related Health Problems; machine learning; medication error; medication safety; Prescribing Information; Summary of Product Characteristics